Electrochemical study of zinc selenide thin films prepared for photovoltaic applications - Mohamad, Souad A.; Arof , A. K. (IIUM, 2012)
Polycrystalline thin films of cubic zinc selenide semiconductor have been electrochemically deposited on conducting substrates of indium tin oxide, ITO glass. Initial investigation with voltammetry was done and the influence of deposition potential and of bath temperature on the films crystallinity is discussed. At room temperature, amorphous films were obtained and at elevated bath temperatures between 55 oC and 75 oC, films were crystallined. The best deposition voltage obtained was -0.95 V vs. Ag /AgCl while at lower deposition potentials, the films do not form well. Energy Dispersive Analysis and X-Ray spectrum indicate that the films deposited at 65 oC and -0.95 V vs. Ag/AgCl have nearly stoichiometric Zn: Se ratio. Energy band gap and refractive index are in agreement with reported results.